Extracorporeal Shockwave Lithotripsy for Cystine Stones in Children: An Observational, Retrospective, Single-Center Analysis - Nicolas Vinit; Antoine Khoury; Pauline Lopez; Laurence Heidet; Laurence Heidet; Nathalie Botto; Olivier Traxer; Olivier Traxer; Olivier Traxer; Olivia Boyer; Olivia Boyer; Olivia Boyer; et al. (Frontiers Media S.A., 2021)
Purpose: Cystinuria is a genetic disorder characterized by a defective reabsorption of cystine and dibasic amino acids leading to development of urinary tract calculi from childhood onward. Cystine lithiasis is known to be resistant to fragmentation. The aim was to evaluate our long-term experience with extracorporeal shockwave lithotripsy (ESWL) used as first-line urological treatment to treat cystine stones in children.Methods: We retrospectively reviewed the charts of all children who underwent ESWL for cystine stone. We assessed the 3-month stone-free rate, according to age, younger (group 1) or older (group 2) than 2 years old.Results: Between 2003 and 2016, 15 patients with a median (IQR) age at first treatment of 48 (15-108) months underwent ESWL in monotherapy. Median age was, respectively, 15 and 108 months in each group. The median (IQR) stone burden was 2,620 (1,202-8,265) mm3 in group I and 4,588 (2,039-5,427) mm3 in group II (p = 0.96). Eleven patients had bilateral calculi. ESWL was repeated on average 2.4 times, with a maximum of 4 for patients of group I, and 4.8 times, with a maximum of 9 for group II (p > 0.05). ESWL in monotherapy was significantly more efficient to reach stone-free status for children under 2 years of age: 83% vs. 6.2% (p = 0.040). The median (IQR) follow-up of the study was 69 (42-111) months.Conclusion: ESWL appears as a valid urological option for the treatment of cystine stones, in young children. Even if cystine stones are known to be resistant to fragmentation, we report 83% of stone-free status at 3 months with ESWL used in monotherapy in children under 2 years old with cystinuria. In older children, the success rate is too low to recommend ESWL as a first line approach.